Post-COVID-19 assessment in a specialist clinical service: a 12-month, single-centre, prospective study in 1325 individuals. Issue 1 (11th November 2021) - Heightman, Melissa; Prashar, Jai; Hillman, Toby E; Marks, Michael; Livingston, Rebecca; Ridsdale, Heidi A; Roy, Kay; Bell, Robert; Zandi, Michael; McNamara, Patricia; Chauhan, Alisha; Denneny, Emma; et al.
Abstract : Introduction: Post-COVID-19 complications require simultaneous characterisation and management to plan policy and health system responses. We describe the 12-month experience of the first UK dedicated post-COVID-19 clinical service to include hospitalised and non-hospitalised patients. Methods: In a single-centre, observational analysis, we report the demographics, symptoms, comorbidities, investigations, treatments, functional recovery, specialist referral and rehabilitation of 1325 individuals assessed at the University College London Hospitals post-COVID-19 service between April 2020 and April 2021, comparing by referral route: posthospitalised (PH), non-hospitalised (NH) and post emergency department (PED). Symptoms associated with poor recovery or inability to return to work full time were assessed using multivariable logistic regression. Results: 1325 individuals were assessed (PH: 547, 41.3%; PED: 212, 16%; NH: 566, 42.7%). Compared with the PH and PED groups, the NH group were younger (median 44.6 (35.6–52.8) years vs 58.3 (47.0–67.7) years and 48.5 (39.4–55.7) years), more likely to be female (68.2%, 43.0% and 59.9%), less likely to be of ethnic minority (30.9%, 52.7% and 41.0%) or seen later after symptom onset (median (IQR): 194 (118–298) days, 69 (51–111) days and 76 (55–128) days; all p<0.0001). All groups had similar rates of onward specialist referral (NH 18.7%, PH 16.1% and PED 18.9%, p=0.452) and were more likely to require support for breathlessness (23.7%, 5.5% and 15.1%, p<0.001) and fatigue (17.8%, 4.8% and 8.0%, p<0.001). Hospitalised patients had higher rates of pulmonary emboli, persistent lung interstitial abnormalities and other organ impairment. 716 (54.0%) individuals reported <75% optimal health (median 70%, IQR 55%–85%). Less than half of employed individuals could return to work full time at first assessment. Conclusion: Post-COVID-19 symptoms were significant in PH and NH patients, with significant ongoing healthcare needs and utilisation. Trials of interventions and patient-centred pathways for diagnostic and treatment approaches are urgently required.